Influence of Business Information Systems, Data Accuracy, System Integration, and User Competency on Decision-Making Effectiveness - Sofalina, Fresa Dwi Juniar (International Journal of Business, Law, and Education, 2026)
In the current digital business environment, organisations use Business Information Systems (BIS) to support managerial and strategic decision-making. Nevertheless, the effectiveness of decisions is not only dependent on the presence of technological systems but also on the accuracy of data, the level of system integration, and the competency of users who operate these systems. The study seeks to analyze the impact of Business Information Systems, data accuracy, system integration, and user competency on decision-making effectiveness. A quantitative explanatory research design was adopted for the study using a survey approach. The data was collected from 120 respondents who actively use Business Information Systems in their organizations. The research instrument was validated for validity and reliability, and the data were analysed using multiple regression to determine the partial and simultaneous effects of the independent variables on decision-making effectiveness. The findings show that Business Information Systems, data accuracy, system integration, and user competency are significantly and positively related to decision-making effectiveness. At the same time, the four variables have a significant impact on decision-making effectiveness, with a coefficient of determination (R²) of 0.611, which means that the model explains 61.100% of the variation in decision-making effectiveness. Among the four independent variables, the most influential factor in decision-making effectiveness is user competency. The findings of this study suggest that, for effective decision-making, organisations need not only accurate and integrated information systems but also accurate data and competent users who can interpret and effectively use the outputs of those systems.